Anomali Fonologi Bahasa Indonesia: Kajian Linguistik Aplikatif - Choirul Anam; Wasilatul Bariroh; Siti Qomariyah; Moh. Raji (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
Phonological linguistic units are a fascinating and varied research focus. Differences in pronunciation from one speaker to another are caused by the abstract and distinctly different language systems in the human mind. Therefore, it is not surprising that many deviations or anomalies are found in the phonological process. This qualitative research presents examples of phonological anomalies in Indonesian, along with pronunciations that are common but do not conform to Indonesian language rules. Data are drawn from empirical experience during the discovery of related language anomalies. The data sources presented cannot be formulated, but recording techniques and memory skills are necessary to ensure the clarity and authenticity of the information (data). This is also driven by the fact that many phonological anomalies are found in the public sphere, so research data no longer needs to be sought or formulated. Researchers simply bring them into the focus of discussion to be analyzed, tested, and researched. The numerous data found (abbreviation: 9 data, words: 17 data) further strengthen the assumption that problematic Indonesian phenomena have become commonplace and normalized.